Penalizing women’s fear: intimate partner violence and parental alienation in Canadian child custody cases - Sheehy, Elizabeth; B. Boyd, Susan (Journal of Social Welfare and Family Law, 2020)
This paper explores Canadian family law cases involving claims of parental alienation and of family violence from 2014–2018, reporting the data on these claims, their resolution, and their impacts upon custody and access. A close reading of those cases where both alienation and intimate partner violence claims are made reveals troubling patterns in how intimate partner violence is discounted in this context. We suggest that the rise of shared parenting as a dominant norm assists in understanding why alienation has achieved such unquestioned status, and call for greater focus on safety and women’s and children’s voices.